2008
DOI: 10.1074/jbc.m804846200
|View full text |Cite
|
Sign up to set email alerts
|

Inactive and Active States of the Interferon-inducible Resistance GTPase, Irga6, in Vivo

Abstract: Irga6, a myristoylated, interferon-inducible member of the immunity-related GTPase family, contributes to disease resistance against Toxoplasma gondii in mice. Accumulation of Irga6 on the T. gondii parasitophorous vacuole membrane is associated with vesiculation and ultimately disruption of the vacuolar membrane in a process that requires an intact GTP-binding domain. The role of the GTP-binding domain of Irga6 in pathogen resistance is, however, unclear. We provide evidence that Irga6 in interferon-induced, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 31 publications
2
83
0
1
Order By: Relevance
“…We used bioinformatic tools to predict transmembrane regions of IRG proteins, which might provide insights into their ability to recruit to membrane compartments. We found that the IRG family members, including IRGB10, contain two putative myristoylation sites at the amino terminus region (Figure S5B), consistent with previous studies reporting the presence of a myristoylation motif in IRGB10 and IRGA6 (also known as IIGP1) (Haldar et al, 2013; Martens et al, 2004; Papic et al, 2008). We further identified two putative transmembrane helices on the carboxyl terminus of IRGB10 and several other IRG proteins, of which putative transmembrane helix 1 is an amphipathic helix and predicted to show antimicrobial potential (Figures S5C and S5D).…”
Section: Resultssupporting
confidence: 91%
“…We used bioinformatic tools to predict transmembrane regions of IRG proteins, which might provide insights into their ability to recruit to membrane compartments. We found that the IRG family members, including IRGB10, contain two putative myristoylation sites at the amino terminus region (Figure S5B), consistent with previous studies reporting the presence of a myristoylation motif in IRGB10 and IRGA6 (also known as IIGP1) (Haldar et al, 2013; Martens et al, 2004; Papic et al, 2008). We further identified two putative transmembrane helices on the carboxyl terminus of IRGB10 and several other IRG proteins, of which putative transmembrane helix 1 is an amphipathic helix and predicted to show antimicrobial potential (Figures S5C and S5D).…”
Section: Resultssupporting
confidence: 91%
“…Immunoreagents used in this study were 3E2 mouse monoclonal antibody against ROP5 isoforms (Leriche and Dubremetz, 1991), anti‐ROP18 rat antiserum (El Hajj and Dubremetz, unpublished), affinity‐purified rabbit sera 87558 against (pT108)Irga6 (Steinfeldt et al ., 2010), 10D7 and 10E7 mouse monoclonal antibodies (Papic et al ., 2008) or 165 rabbit antiserum (Martens et al ., 2004) against Irga6, B34 mouse monoclonal antibody (Carlow et al ., 1998) against Irgb6, 940/6 rabbit antiserum (unpublished) against Irgb10, 2078 rabbit antiserum (Martens et al ., 2004) against Irgd, 3.1.2 and 2.4.21 rat monoclonal antibodies against T. gondii GRA7 (unpublished), and rabbit anti‐calnexin antiserum (Calbiochem).…”
Section: Methodsmentioning
confidence: 99%
“…Parasites were allowed to invade for 30 min at 37°C after which the coverslips were washed 3 times with PBS, fixed with 4% formaldehyde PBS, and permeabilized with 0.05% Triton X-100 in PBS. Coverslips were blocked in 10% goat serum (Life Technologies) PBS and then stained with the mouse monoclonal antibody 10D7, which recognized GTP-bound Irga6 59 , at a 1:500 dilution and the rabbit polyclonal anti-TgAldolase 60 at 1:1,000. Alexa-fluor conjugated secondary antibodies were applied at 1:1,000 and counterstained with 0.1 μg/ml Hoechst 33258.…”
Section: Methodsmentioning
confidence: 99%